Developing the Learning Media Based on E-Learning at Accounting Subject for Senior High School - Wardoyo, Cipto (Dinamika Pendidikan, 2016)
Learning media have the very important role in the learning process. The learning media help the process of delivering information from teachers to students. The learning media also make something abstract and difficult for students to be clearer and easier to be understood. Along with the technological development, the media existence based on computer are widely used as the alternative learning media. The objective of the study was to create the accounting learning media based on e-learning using Moodle software; it was one of e-learning applications which could be used in the learning activities and it was easy to be created. Â It was a Research and Development study using Borg and Gall model. The stages of the study were: 1) the initial needs analysis, 2) the initial product development, 3) the expert validation, 4) the first revision; 5) the limited field tests 6) the second revision, 7) the final product. The material validation was performed by the materials experts; whereas the media validation was performed the media experts and users (students). The results showed that there was 100% validated by the material experts and 96.67%, by the media experts; 81.49% was from the users (students); thus the average validation was 92.72%. It means that the learning based on e-learning for accounting subject with Moodle application was very suitable. Thus; it is suggested for the teachers to use the learning media based on e-learning in the learning process. Then, facilities and infrastructure in the classroom should be adequate to support the optimal utilization of the media.